Design Of Accounting Recording System At Bimbingan Belajar Rumah Cerdas - Natasha Antonia Wisely; Ria Karina (Universitas Internasional Batam, 2023)
Bimble Rumah Cerdas is a business engaged in the service sector which located at Kavling Sagulung Lama Gang Salak Blok A No 4 Batam. Bimble Rumah Cerdas is facing problems in financial recording which is only done manually, and does not present a financial report. Based on these problems, the solution to help the business owner is to design a simple accounting system and produce a reliable financial report. This system is designed using Microsoft Access according to business needs. The resulting financial statements are in the form of income report, expense report, changes on equity statements, income statements, financial position reports. The accounting system is also able to produce accounting information that helps owner to make the right decisions so that the business can develop for the better business. The system designed by the author is still relatively simple and can still be improved, so recommendations for future researchers are expected to be able to update the accounting system in accordance with the times that will occur in the future.